(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Lactic acid bacteria (LAB) present in fermented foods has long been consumed by humans without any obvious adverse effects. Therefore, they are potent candidates as vehicles for the delivery of digestive enzymes. Stachyose, a tetrasaccharide, is believed to contribute to flatulent properties of soyabeans that limit their use for human consumption. LAB including some Lactobacillus plantarum, L.fermentum,L. buchneri and reuteri hydrolyze α- galactosides or non-digestible carbohydrates into digestible carbohydrates during fermentation. These bacteria are therefore a source of α -galactosidase. If soy milk could be fermented with these microorganisms that utilize stachyose either to produce acid or to hydrolyze it to mono and disaccharides, the product thus prepared ought to be less flatulent and therefore, more acceptable. In present study, total 27 lactic acid bacteria were recovered selectively on MRS agar from the various milk and milk products. All the 27 isolates were characterized morphologically and the colonies were white to cream and gram positive. Out of 27 LAB only 5 isolates were found to be positive for α- galactosidase enzyme. α-galactosidase activities were determined by using p-NPG. All 5 α- galactosidase producer were further subjected for various biochemical characterization for partial identification and were catalase negative, and casein hydrolysis, sugar fermentation, nitrate reduction positive. Reduction of α- galactosides by the 5 selected isolates were evaluated. The isolate, RLAB α-4, CLAB α-14, CLAB, CLAB α-20 α-18 and WLAB α-25 degraded 67.56 %, 45.94%, 54.05%, 70.27%, and 64.86% α- galactosides respectively. CLAB α-20 degraded maximum concentration of α- galactosides and RLAB α-14 degraded least concentration of α- galactosides.